Study on the impact toughness and diffusible hydrogen of G105 drill pipe steel in wet H2S environment. (18th August 2017) - Huang, Bensheng; Peng, Hao; Chen, Xiang; Gong, Chenglong; Li, Jiachen
ABSTRACT: In order to investigate the influence of wet H2 S environment on impact toughness of G105 drill pipe steel, the impact test of drill pipe exposed to NACE A solution for different time was carried out. Meanwhile, the diffusible hydrogen concentration was measured to study the relationship between diffusible hydrogen and impact toughness damage. The results suggest that with the increase of corrosion time, the impact energy of G105 drill pipes decreases from 107.7 to 88.4 J, and the dynamic fracture toughness decreases gradually. The impact toughness damage increases as the diffusion hydrogen concentration increases. However, the impact energy recovery happened after hydrogen releasing. The quasi-cleavage features occur with the increasing of hydrogen concentration.